Effects of freezing pork chops on warner-bratzler shear force and cookery traits - Andrews, B.S.; Unruh, John A.; Hunt, Melvin C.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty-one boneless pork loins were used to determine the influence of freezing and pH on Warner-Bratzler shear force (WBS) values and cookery traits. Chops with lower pH (<5.5 to 5.5) had higher cooking losses than chops with intermediate pH (5.7 to 5.9) and higher pH (6.0 to >6.2). Similar to cooking losses, total moisture losses decreased with increased pH. Frozen chops had lower WBS values (more tender) than fresh chops. However, fresh chops had a higher total yield (lower moisture loss) than frozen chops.
Keywords: Swine; Pork; Quality; Freezing